Addressing gross motor function by functional repetitive neuromuscular magnetic stimulation targeting to the gluteal muscles in children with bilateral spastic cerebral palsy: benefits of functional repetitive neuromuscular magnetic stimulation targeting the gluteal muscles - Grosse, Leonie; Späh, Malina A.; Börner, Corinna; Schnabel, Julian F.; Meuche, Anne C.; Parzefall, Barbara; Breuer, Ute; Warken, Birgit; Sitzberger, Alexandra; Hösl, Matthias; Heinen, Florian; Berweck, Steffen; et al. (Frontiers in Neurology, 2023)
Background Impaired selective motor control, weakness and spasticity represent the key characteristics of motor disability in the context of bilateral spastic cerebral palsy. Independent walking ability is an important goal and training of the gluteal muscles can improve endurance and gait stability. Combining conventional physical excercises with a neuromodulatory, non-invasive technique like repetitive neuromuscular magnetic stimulation probably enhances effects of the treatment. This prospective study aimed to assess the clinical effects of repetitive neuromuscular magnetic stimulation in combination with a personalized functional physical training offered to children and adolescents with bilateral spastic cerebral palsy. Methods Eight participants Gross Motor Function Classification System level II and III (10.4 ± 2y5m; 50% Gross Motor Function Classification System level II) received a personalized intervention applying functional repetitive neuromuscular magnetic stimulation (12 sessions within 3 weeks; 12,600 total stimuli during each session). At baseline and follow up the following assessments were performed: 10-m-walking-test, 6-min-walking-test, GMFM-66. Six weeks after the end of treatment the patient-reported outcome measure Gait Outcome Assessment List was completed. Results GMFM-66 total score improved by 1.4% (p = 0.002), as did scoring in domain D for standing (1.9%, p = 0.109) and domain E for walking, jumping and running (2.6%, p = 0.021). Gait speed or distance walked during 6 min did not improve from baseline to follow up. Patient-reported outcome showed improvement in 4 patients in altogether 14 ratings. Caregiver-reported outcome reported benefits in 3 participants in altogether 10 ratings. Conclusion Repetitive neuromuscular magnetic stimulation promises to be a meaningful, non-invasive treatment approach for children and adolescents with bilateral spastic cerebral palsy that could be offered in a resource-efficient manner to a broad number of patients. To further investigate the promising effects of repetitive neuromuscular magnetic stimulation and its mechanisms of action, larger-scaled, controlled trials are needed as well as comprehensive neurophysiological investigations.